No verão, açaí; no inverno, camarão: tempo e práticas econômicas na ilha de Paquetá (Belém-Pará) - LOPES, João Luiz da Silva (2006)
It addresses the life of a social segment living by the Amazon, historically called ribeirinho (the ones from the river), and sometimes interpreted as isolated and destined to disappear. The approach of this research considers on the concrete socio-environmental experience of a small social group on the insular area of the Town Belém. The analysis of the relation between the temporal consciousness and the realization of the productive practices, in the perspective of the social sciences through a fieldwork of qualitative nature, guided this study. The results of this research suggested the necessity of the abandon of the simplistic, homogenizing and dichotomist analyses, and the building of a complex framework that permits the perception of the co-existence, the tension, the antagonism, the conflict and the complementarities, simultaneously among several periods. This social segment guarantees its reproduction, despite the dominant economical processes, through a strategy that combines the ecological time and the mechanical time, the traditional time and the modern time, the production destined to self-consume and the production destined to commercialization, contradicting the theories that predict its disappearance.